Cornish Methodism, revivalism, and popular belief, c. 1780-1870 - Luker, D; Luker, D. H. (1988)
In this regional study of Methodist development and societal influence throughout the period of industrialisation, recent trends in Methodist historiography at a national level are combined with the research and source material accumulated at a local level, to provide a detailed analysis of Methodist growth in Cornwall between the years 1780 and 1870. The thesis is divided loosely into three sections. In the first, four chapters outline the essential background to interpretative analysis by considering, in turn, recent historiographical developments in Methodist studies; social change in Cornwall during industrialisation; the performance of the Anglican Church in the county as represented in the Visitation Returns for 1779, (as well as historical and structural reasons for its 'failure'); and Methodist growth as expressed through available statistical indices, especially the date of formation of Methodist societies, and the 1851 Ecclesiastical Census. In the second section, one long chapter is devoted to an in-depth, county-wide analysis of Methodist growth, which considers the impact of external factors, particularly socio-economic, and internal circumstances, such as the degree of maturity of pastoral and administrative machinery, and the level of Connexional or lay control over chapel and circuit affairs, on the form and function of Methodism in nine distinct socioeconomic regions within the county. In the third section, four chapters concentrate on West Cornwall, where Methodism was strongest, in order to examine the roots of, and reasons for, the distinctively indigenous form of Methodism which developed there. On the one hand, the pastoral and administrative difficulties in exerting adequate Connexional control are considered; while on the other, an interpretation of the 'folk' functionality of revivals and of Methodism as a 'popular religion' is offered.